Analysing the transport phenomena of novel dew-point evaporative coolers with different flow configurations considering condensation. (May 2021) - Wan, Yangda; Huang, Zhifeng; Soh, Alexander; Cui, Xin; Chua, Kian Jon
Highlights: A novel dew-point evaporative cooler with a closed-loop arrangement is proposed. The pre-cooling, energy recovery and dehumidification are simultaneously achieved. The effects of the various parameters on the cooling performance are studied. A comparative study on the cooler with different configurations is carried out. Abstract: This paper entails a study on the transport phenomena of a novel dew-point evaporative cooler with counter-flow closed-loop configuration, a potential alternative to the conventional mechanical vapor compression system. In contrast to the conventional indirect evaporative cooler and the regenerative indirect evaporative cooler, the proposed novel dew-point evaporative cooler is capable of achieving the simultaneous goals of pre-cooling, energy recovery and dehumidification. The novel dew-point evaporative cooler is classified as either type 1 or type 2 based on the relative flow direction between the water and the supply air. A two-dimensional computational fluid dynamics model is judiciously developed and employed to conduct a comparative study which evaluates the performance of the conventional indirect evaporative cooler vis-a-vis both novel type 1 and novel type 2 configurations. Experimental data is then employed to validate the predictive accuracy of the mathematical model. The distributions of both temperature and humidity ratio are plotted for a typical case of the novel cooler incorporating both flow configurations and considering the effects of moisture condensation. Additionally, the impacts made by key parameters on the cooling performance under condensation state are analyzed by using three evaluation indexes, namely, latent efficiency, wet-bulb efficiency, and enlargement coefficient. By regulating several operating parameters, the variations of the three evaluation indexes are plotted via the proposed numerical model. Key results from this study revealed that the novel type 1 flow configuration is capable of achieving the highest latent and wet-bulb efficiencies, and enlargement coefficient. It is also observed that the relative flow direction between the water and the supply air exerts a stronger influence on the cooler performance compared to the changes of the water mass flow rate.